Animals that build their homes - McClung, Robert M. ([Washington] : National Geographic Society, 1976)
Text and photographs discuss animals that build their own homes including beavers, crayfish, and bees.
Keywords: Animals -- Habitations -- Juvenile literature; Animals -- Habitations; Animals -- Habits and behavior